Prevalence of cyber plagiarism among MBA students - Liyanage, M.P.P. (My University, 2012)
In the present digital era, plagiarism is widely spoken of as an issue which is relevant to the academia due to the increase in academic dishonesty. With the availability and easy access of cyber information, copying and pasting information from the online resources has become a trend among many students. This research focuses on observing-the prevalence of cyber plagiarism among MBA students in public higher education establishments in the Colombo district of Sri Lanka. From a sample of 214 students, 134 valid questionnaires were used for the analysis. The Questionnaire addressed the issues of the extent of cyber plagiarism among MBA Students, the frequent types of cyber plagiarism, prominent factors affecting towards cyber plagiarism and influence of demographic characteristics to prominent factors affecting towards cyber plagiarism among MBA students. The results of the analysis indicate that 37.9% (50 out of 132) did not plagiarize and majority of 62.1% (82 out of 132) plagiarized. According to the student point of view the most frequent type of cyber plagiarism activity was unacceptable paraphrasing and most prominent factor affecting towards cyber plagiarism were deadlines suddenly looming over the horizon. In accordance with the analysis, some of the demographic ) characteristics influence upon the factors affecting towards cyber plagiarism and some others do not influence or are independent from the factors affecting towards cyber plagiarism. The outcome of the study could help the academics to educate the students on how to avoid academic dishonesty, cyberplagiarism and create a better awareness about fair use of information. The research concludes by providing an insight into the limitations of the research and indicates the parameters for further research directions emerging out of this research. v